Potential Plasticity of Artificial Feed Preference in Juvenile Pharaoh Cuttlefish (Sepia pharaonis) Through Progressive Training Programs - Ma, Chia-Huan; Lin, Chih-Hung; Chang, Yung-Cheng; Lee, Hung-Tai; Liou, Chyng-Hwa; Hsu, Te-Hua (Frontiers in Marine Science, 2022)
The cuttlefish is a commercially important marine species globally; however, a lack of appropriate artificial feed limits its future aquaculture development. We propose a novel process comprising a (1) feed preference tests and (2) progressive training programs. Through this process, artificial diets can become more suitable for pharaoh cuttlefish (Sepia pharaonis). Feed preference tests (based on vision, touch, and smell) revealed that pharaoh cuttlefish preferred rod-shaped feed over flat rod–shaped or ball-shaped feed, moist feed over dry feed, and dry feed with agar coating over dry feed without agar coating. Without olfactory training, some cuttlefish refused to eat artificial feed and eventually died. Through progressive training programs (3-week and 6-week programs), a survival rate of >80% was achieved. Although the artificial diets examined in this study resulted in a lower conversion ratio for S. pharaonis than for fresh shrimp, available artificial feed can potentially be adopted for cuttlefish aquaculture through the use of our progressive training program.